2008
DOI: 10.1038/sj.jid.5701079
|View full text |Cite
|
Sign up to set email alerts
|

Further Exploring the Brain–Skin Connection: Stress Worsens Dermatitis via Substance P-dependent Neurogenic Inflammation in Mice

Abstract: A neurogenic component in atopy and allergy is evident and potentially of great pathogenic relevance. Stress was recently shown to activate elements of this component and is vividly discussed as a cause of exacerbation. However, to date, scientific proof of stress-induced neuronal plasticity and neuro-immune interaction in atopy or allergy remains lacking. Here we show early evidence that exposure to sound stress and atopic dermatitis-like allergic dermatitis (AD) equipotently raise the number of cutaneous ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
151
0
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(169 citation statements)
references
References 102 publications
9
151
0
7
Order By: Relevance
“…Another study showed mast cells express the NK-1 receptor in both affected and unaffected psoriatic skin (6). NK-1 is also important in stress-induced murine skin mast cell activation (3,16), and in the development of atopic dermatitis in mice (68). In fact, stress increases SPpositive nerve fibers and mast cell contacts in mice (69), whereas an NK-1 receptor antagonist inhibits stress-induced mast cell degranulation in mice (72).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study showed mast cells express the NK-1 receptor in both affected and unaffected psoriatic skin (6). NK-1 is also important in stress-induced murine skin mast cell activation (3,16), and in the development of atopic dermatitis in mice (68). In fact, stress increases SPpositive nerve fibers and mast cell contacts in mice (69), whereas an NK-1 receptor antagonist inhibits stress-induced mast cell degranulation in mice (72).…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells are often located close to SP-positive neuronal processes (66)(67)(68)(69). Mast cell-neuronal interactions might be involved in the pathophysiology of psoriasis and might participate in the exacerbation of symptoms by stress (7,13,70).…”
Section: Discussionmentioning
confidence: 99%
“…Both human and animal model studies demonstrated the importance of RBFOX1 in neuronal development and regulation (40,41). Although the connection between neurologic stimulation and atopic disease remains to be elucidated, it is noteworthy that stress can exacerbate atopic dermatitis via substance P-dependent neurogenic inflammation (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of stress in cutaneous neurogenic inXammation and sensory nerve-mast cell interaction has been suggested in several studies [6,143]. Neuropeptides SP and VIP can eYciently activate human skin mast cells for rapid histamine release in situ [71] and in vitro [23].…”
Section: Interactions Between Mast Cells and Sensory Nerves In Psoriasismentioning
confidence: 99%